Change in body mass index within the first-year post-injury: a VA Traumatic Brain Injury (TBI) model systems study. (3rd July 2018) - Brown, Racine Marcus; Tang, Xinyu; Dreer, Laura E.; Driver, Simon; Pugh, Mary Jo; Martin, Aaron M.; McKenzie-Hartman, Tamara; Shea, Timothy; Silva, Marc A.; Nakase-Richardson, Risa
ABSTRACT: Objective : To describe change in body mass index (BMI) and weight classification 1-year post- traumatic brain injury (TBI) among Veterans and service members. Design : Prospective observational cohort study. Setting : VA Polytrauma Rehabilitation Centers. Participants : Veterans and service members ( N  = 84) enrolled in VA Traumatic Brain Injury Model Systems (VA TBIMS) study with BMI scores at enrollment and 1-year post-injury. Interventions : N/A. Main outcome measures : BMI scores from height and weight and weight classifications (underweight, normal weight, overweight, obese classes 1–3) defined by WHO. Results : Twenty per cent were obese at time of injury and 24% were obese at 1-year post-injury. Cross-tab analyses revealed 7% of normal weight and 24% overweight participants at time of injury as obese Class 1 one-year post-injury. Univariate models found BMI and tobacco smoking at time of injury were significant predictors of higher BMI scores 1-year post-TBI. Multivariable models found BMI at time of injury and motor functioning, were significant predictors. Preinjury BMI, tobacco smoking and PTSD symptom severity predicted change in weight category. Conclusion : While obesity among service members and Veterans post-TBI is below national averages, trends in weight gain between time of injury and 1-year follow-up were observed. Implications for health promotion and chronic disease management efforts with regards to rehabilitation for injured military are discussed. List of Abbreviations : BMI, Body mass index; BRFSS, Behavioural Risk Factor Surveillance; GCS, Glasgow Coma Scale; FIM, Functional Independence Measure; NIDILRR, National Institute on Independent Living and Rehabilitation Research; PCL-C, PTSD checklist-civilian; PSTD, Post-traumatic stress disorder; VA, Veterans Affairs; VA PRC, Veterans Affairs Polytrauma Rehabilitation; VA TBIMS, Veterans Affairs TBI Model Systems;